2020
DOI: 10.3390/coatings10020099
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Origin and Deacetylation Degree of Chitosan on Properties of Its Coatings on Titanium

Abstract: The properties of chitosan coatings on titanium surfaces may be influenced by a variety of factors, including their chemical characteristics and the deposition method. The aim of this research was to determine the influence of a chitosan’s origin (a type of shrimp) and deacetylation degree (DD), when deposited on a very smooth titanium surface, on adhesion and biological behavior. The tests were performed using chitosan of a degree of 87% or 84% of deacetylation and that originated from armor crabs or shrimp a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…40 Hence, it is reasonable to implement such surfaces with substances with antimicrobial efficiency. The obtained contact angle values are similar to those reported so far, for chitosan in the range of 70 -75 , 41 and PVP of 60 -75 . 42 EE100 coatings alone exhibit hydrophobic properties (contact angle of about 109 ).…”
Section: Discussionsupporting
confidence: 89%
“…40 Hence, it is reasonable to implement such surfaces with substances with antimicrobial efficiency. The obtained contact angle values are similar to those reported so far, for chitosan in the range of 70 -75 , 41 and PVP of 60 -75 . 42 EE100 coatings alone exhibit hydrophobic properties (contact angle of about 109 ).…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the degree of deacetylation can also affect the values of the CA. For instance, Supernak-Marczewska et al [58] demonstrated that the CA increased with the increase in deacetylation degree value. These results support the lower CA of CS3, as its deacetylation degree is lesser than CS1 and CS2 or CS5 and CS6.…”
Section: Characterization Of the Pe-modified Surfacesmentioning
confidence: 99%
“…Enzyme immobilization technique that has been developed recently is by means of adsorption on the surface of solids or membranes [28]. Enzymes can be more durable or less easily damaged when immobilized in a membrane, where the enzyme is separated in the pores of the membrane [29].…”
Section: Introductionmentioning
confidence: 99%